Milk production capacity of prolific Priangan sheep: Preweaning performance - Tiesnamurti, Bess; Inonou, Ismeth; ., Subandriyo (Indonesian Animal Sciences Society, 2002)
A study was conducted to investigate the milk production capacity and preweaning performance of the prolific Priangan sheep, at sheep breeding station of the Research Institute for Animal production, Bogor using 126 ewes during three lambing periods in three consecutive years. The milk production was estimated weekly, started at day 7 after lambing date, till lambs were weaned at 90 days of age. The results showed that total milk production was significantly affected (P<0.05) by parity and the number of lambs born with average daily milk production of 519.5 g head-1 day-1. Estimated total milk production was 43.6 kg/lactation (N = 126; SD = 7.8; CV = 19.4%; range = 28.7-53.6 kg). According to the dam parity, the highest milk production was estimated at third parity (40.1 kg head-1 lactation-1), whereas on the basis of litter size, ewes with twin born lamb had the highest production (39.9 kg head-1 lactation-1). The preweaning lamb performance (weaning weight and preweaning daily gain) was significantly affected (P<0.05) by ewe parity, sex, litter size and type of birth and weaned, with the average weaning weight of 10.62 kg (N = 208; SD = 3.37; CV = 25.08%) and 130.9 + 41.8 g head-1 day-1 (N = 208; SD = 33.5; CV = 31.26%), respectively. Where as lamb birth weight was significantly affected (P<0.05) by ewe parity, sex and the number of lambs bornwith average of 2.39 kg (N = 208; SD = 0.66; CV = 9.8%). Key words: Milk production, prolific sheep, preweaning performance